Normal saline instillation versus no normal saline instillation And lung Recruitment versus no lung recruitment with paediatric Endotracheal Suction: the NARES trial. A study protocol for a pilot, factorial randomised controlled trial. Issue 1 (31st January 2018) - Schults, Jessica A; Cooke, Marie; Long, Debbie A; Schibler, Andreas; Ware, Robert S; Mitchell, Marion L
Abstract : Introduction: Endotracheal suction (ETS) is a frequent and necessary airway intervention for the intubated child. The aim of ETS is to clear the endotracheal tube and airways of respiratory secretions; however, the methods of performing ETS are varied. Internationally a number of ETS treatments are in use. Many have not been rigorously evaluated in a randomised controlled trial setting, and it is uncertain whether any are associated with better outcomes for the critically ill child. With approximately 50% of paediatric intensive care admissions requiring intubation, ETS interventions that maximise the efficacy and minimise the complications of ETS could translate to improved health for substantial numbers of critically ill children, and significant cost savings. The primary aim of the study is to examine two ETS interventions, normal saline instillation and lung recruitment, to determine if it is feasible to conduct a full efficacy trial. Methods and analysis: NARES (Normal saline instillation versus no normal saline instillation And lung Recruitment versus no lung recruitment with paediatric Endotracheal Suction) is a single-centre, pilot, factorial randomised controlled trial conducted in a tertiary referral paediatric centre in Brisbane, Australia. Children (aged 0–16 years) are eligible if they are intubated with an endotracheal tube and mechanically ventilated. Two intervention pairs will be compared using a 2×2 factorial design: (1) normal saline instillation versus no normal saline instillation; and (2) lung recruitment versus no lung recruitment. The primary outcome is study feasibility measured by a composite analysis of eligibility, recruitment, retention, protocol adherence and missing data. Secondary outcomes are ventilator-associated pneumonia, SpO2 /FiO2 ratio, lung compliance, end expiratory level and regional tidal volume. Ethics and dissemination: Ethical approval to conduct the research has been obtained. Dissemination of the research findings will be untaken, guided by the Consolidated Standards of Reporting Trials statement recommendations. Protocol content was guided by the Standard Protocol Items: Recommendations for Interventional Trials 2013 statement. Trial registration number: ACTRN12617000609358 ; Pre-results.